1995
DOI: 10.1093/infdis/172.1.305
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 Is a Circulating Mediator in Typhoid Fever

Abstract: The following full text is a publisher's version. For additional information about this publication click this link.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…The serum PLA 2 concentrations in severe inflammatory conditions such as typhoid fever (17) and systemic fungal infections (18) have been reported to be ϳ1-5 g/ml. In normal human tears the concentration of group IIA PLA 2 exceeds 30 g/ml (4).…”
Section: Discussionmentioning
confidence: 99%
“…The serum PLA 2 concentrations in severe inflammatory conditions such as typhoid fever (17) and systemic fungal infections (18) have been reported to be ϳ1-5 g/ml. In normal human tears the concentration of group IIA PLA 2 exceeds 30 g/ml (4).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of group II PLA2 in sera of PLA2 ϩ mice was somewhat higher (approximately 2,500 g/liter) (16) than that found in humans with severe infectious diseases. These diseases include bacterial infections (240 g/liter) (29), sepsis (880 g/liter) (25), peritonitis (440 g/liter) (25), and typhoid fever (1,440 g/ liter) (13). The PLA2 ϩ mice used in the present study showed no clinical symptoms of inflammation and behaved normally despite the exceedingly high PLA2 catalytic activity (up to 100-fold higher than in PLA2 Ϫ mice) and concentration of group II PLA2 in their sera.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the presence of cytokines inhibitors were necessary to counterbalance the high values of proinflammatory cytokines. The same authors studied the influence of blood peripheral 14 kDa group II phospholipase A2 (PLA2) in 12 patients with typhoid fever, after admission and after recovery 30 . On admission, PLA2 levels were high (1444 ± 1560 ng/ml), and decrease gradually to 55 ± 48 ng/ml at 14th day.…”
Section: ) Clinical Manifestations Of Typhoid Fever and Their Pathogmentioning
confidence: 99%
“…Patient with complicated typhoid fever had significantly higher PLA2 levels on admission (2520 ± 48 ng/ml). The authors suggest that PLA2 may be a mediator of seriousness in prolonged inflammatory diseases such as typhoid fever 30 .…”
Section: ) Clinical Manifestations Of Typhoid Fever and Their Pathogmentioning
confidence: 99%